Analisis Faktor Kinerja Pemilik UMKM Makanan dan Minuman dengan Mediasi Keunggulan Bersaing di Surabaya - Muljaningsih, Sri (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
This study aims to determine the effect of Entrepreneurial Orientation, Strategic Assets, andSupply Chain Management on the Performance of MSME Owners through CompetitiveAdvantage in all SMEs registered at the Surabaya City Trade Office with sampling techniquesusing the census method and Partial Least Square (PLS) data analysis techniques. The research results show that: 1) Entrepreneurship orientation does not contribute to the performance of MSME owners; 2) Strategic assets can contribute to the performance of MSME owners; 3) Supply Chain management does not contribute to the performance of MSME owners; 4) Entrepreneurship orientation contributes to the performance of MSME owners through competitive advantage; 5) strategic assets contribute to the performance of MSME owners through competitive advantage; and 6) Supply Chain management contributes to the performance of MSME owners through competitive advantage.